Giant palaeo-landslide dammed the Yangtze river - Higgitt, David L.; Zhang, Xinbao; Liu, Weiming; Tang, Qiang; He, Xiubin; Ferrant, Sylvain (SpringerOpen, 2014)
Field evidence is presented to demonstrate that a very large landslide blocked the Jinsha River (the main stem of the Yangtze) near the present day town of Qiaojia, Yunnan Province. The discovery is significant because no persistent river-blocking landslide has been reported so far downstream in a major catchment. At the location of the landslide dam the upstream catchment area is 445 × 103 km^2. Sediments deposited behind the dam indicate that the minimum crest height was approximately 200 m with a lake volume of 11.4 +/− 1.3 km^3. The landslide occurred on the western (Sichuan) side of the river and displaced an estimated volume of at least 3.75 km^3, with material riding up to 550 m above the river on the eastern (Yunnan) side of the valley. The location is at the intersection of the Xiaojiang and Zemuhe fault zones which form part of the eastern boundary fault of the Sichuan-Yunnan Fault Block, an area where many earthquakes exceeding magnitude 7.0 have been documented in the historical record.